Kecak Touristic Performance in Uluwatu Temple: Its Aspects of Vocal Karawitan - I Putu Ikka Darmawan; Ni Wayan Ardini; I Gede Mudana (Bali Membangun Bali: Jurnal Bappeda Litbang, 2020)
The writers conducted the process of observation, literature study, and interviews with the head of Karang Boma Studio, Pecatu Village to get information related to the Kecak performance at Uluwatu Temple. The uniqueness of this Kecak art can be seen in the presentation that uses human voice accompaniment. Processing melodies and interlocking cak patterns really requires strong breathing. The aesthetic value can be seen from the wholeness in the presentation of Kecak which is presented in its entirety with the patterns arranged in the Kecak's vowels by highlighting the harmonious vocal processing techniques between plain and sangsih cak. The balance in the presentation of Kecak is seen from the melody processing and cak pattern pronunciation that is dynamically balanced and does not occur as a dominant one.